Physiology of domestic animals - Reece, William O. (Lea & Febiger, 1991)
This textbook covers the basics of physiology . The book is divided into 15 chapters, each one dealing with a specific "body system". Covering all of aspects veterinary medicine or veterinary technology. It also includes study aids and review questions